Improving energy efficiency in private rented housing: Why don't landlords act?. Issue 7 (November 2015) - Ambrose, Aimee R
The private rented sector in England contains some of the least energy efficient properties in the country and houses more vulnerable households than any other sector. Occupants endure dangerously cold homes and fuel poverty but have no direct influence over the energy performance of their homes. The choices that occupants make regarding energy are constrained by the material characteristics of a property: something only the landlord can alter. Enduringly poor conditions in the sector indicate that an initiative that convinces landlords of the benefits of improving energy efficiency remains elusive. Based on a review of existing research and 30 interviews with landlords, this paper identifies factors which deter landlords from acting to improve energy efficiency. Factors include lack of knowledge regarding the consequences of energy inefficiency and possible solutions, the absence of direct financial incentives (the principal–agent problem), local housing market and cultural factors. It also identifies a number of motivating factors that may encourage landlords to invest in energy efficiency. It is argued that policies to tackle energy inefficiency in the sector should take account of these factors in order to improve effectiveness.